Into the spotlight [videorecording (DVD)] - Anderson, Erin; Appelman, Nancy (Freestyle Digital Media, 2025)
A heartfelt story of how a script, a stage, and a theater program composed of adults with disabilities celebrate their creativity, explore life's complexities, and empower a community, in their own words and their own way.